Sistem Informasi Penjualan Sparepart Mobil Menggunakan Aplikasi Java Berbasis Unified Modeling Languange (UML) - Puspita, Ari; Lestari, Ade Fitria; Amalia, Hilda (STMIK ANTAR BANGSA, 2019)
Abstract— Star Motor Perkakas is engaged in spare parts, the sales system is still manual with the main help of paper. Employees will record the names of items that have been sold in a book, and employees also make mistakes because they forget to record the names of items that are sold out, so that in searching for items that are requested or ordered experience errors, and it also causes errors in making reports every month. This information system design is expected to be the best solution to solve problems that occur in this company, especially in the management of sales data that is more effective and efficient. This system uses the Netbeans Java and Mysql programming languages as databases. This sales system is also expected to be a sales data management activity to facilitate employees Tools for faster and more accurate transactions. Intisari— Perancangan sistem informasi ini diharapkan menjadi solusi terbaik untuk memecahkan permasalahan yang terjadi dalam perusahaan ini terutama dalam pengelolaan data penjualan yang lebih efektif dan efesien. Sistem yang digunakan ini menggunakan Bahasa pemrograman Java Netbeans dan Mysql sebagai database. Sistem penjualan ini juga diharapkan menjadi kegiatan pengola data penjualan untuk dapat mempermudah pegawai CV. Star Motor Perkakas dalam melakukan transaksi yang lebih cepat dan teliti . Kata Kunci : Forward Chaining, Penjualan, Sistem Pakar